Meta-Analysis of Volatile Compounds from Vinegar Produced by the Slow Method and the Fast Method - Arifatulhuda Rifka; Novelina Novelina; Rina Yenrina (Asia Pacific Network for Sustainable Agriculture, Food and Energy (SAFE-Network), 2022)
Volatile compounds are one of the important characteristics of vinegar, where the content and composition of these compounds is an account for the aroma profile of vinegar. The difference in production technology used in making vinegar produces vinegar with different characteristics. There are two general methods commonly used in the production of vinegar, namely the slow method and the fast method. This meta-analysis was used to conclude several studies that examined the differences in volatile compounds in vinegar produced through the slow methods and the fast methods. From this study, it can be seen that comparison of volatile compounds characteristics in vinegar produced by the slow method and the fast method where the slow method tends to produce vinegar with a high concentration of acetate ester group and alcohol group, and the fast method tend to produce vinegar with a high concentration in a volatile acid group.